PEMANFAATAN REMITAN OLEH KELUARGA TENAGA KERJA INDONESIA UNTUK MENDUKUNG PEMENUHAN KEBUTUHAN KELUARGA DI DAERAH ASAL - Alvino, Putu Gede; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 10 (2020): VOL 9 NO 10, OKTOBER 2020 (2152 - 2389), 2020)
Family welfare is the ability of a family to meet their needs. In order to achieve prosperity, a family member must abroad as an Indonesian Worker (TKI) to fulfill his daily needs. The purpose of this study to analyze effect of remittance delivery frequency, number of remittances, and the number of dependents of families in the area of ??origin simultaneously and partially on the welfare of Indonesian Workers' families, analyze the use of remittances by families of Indonesian workers in Jembrana Regency. Samples 72 families, with purposive sampling. Data collection was carried out through questionnaires and interviews. Analysis technique used multiple linear regression. The results is frequency of sending remittances, the number of remittances, and the number of family dependents simultaneously had a significant effect on the welfare of the families of Indonesian Workers in Jembrana Regency. The frequency of remittance partially positive significant impact on the welfare of Indonesian Workers' families. The number of remittances partially positive significant effect on the welfare of the families of Indonesian Workers. The number of dependents partially negatively affects the welfare of Indonesian Workers' families. Keywords: remittance delivery frequency, remittance, number of family dependents, fulfillment of family needs in the area of ??origin.